Training Application Android for Detection Early Disease Leprosy on Child to Teacher School Base in Region Work Public Health Center Karangploso - Supriadi, Supriadi; Aditya, Ronal Surya; Ramadhan, Muhammad Putra; Zainiyah, Nanik; Rahmatika, Qory Tiffani (Inovasi Lokal, 2023)
Previously done accompaniment but in the adult and elderly groups. Assistance for school children will help all groups to prevent the recurrence of the leprosy endemic in the area Karangploso Community Health Center. Stage First is stage preparation. Stage This started from process planning which includes identifying needs or problems. From the results of the interview with Community Health Center officers in the P2P polyclinic and Promkes sections, results were obtained that the Ketawang Community Health Center has never conducted leprosy detection training child. Based on data from the Community Health Center. Evaluation of cadre skills is evaluated by making direct observations moment cadre use application android For detection early leprosy. Results observation shows that all teachers are able to operate the various features contained in application as well as capable do detection early leprosy on child. Activity This nature sustainable with do monitoring evaluation form accompaniment Which done by team community service to target schools. Assistance for school children will help all groups to prevent the recurrence of the leprosy endemic in the area Karangploso Community Health Center.